High level of treatment failure with commonly used anthelmintics on Irish sheep farms - Keane, Orla M (BioMed Central, 2014)
BACKGROUND: In 2013 a Technology Adoption Program for sheep farmers was established to encourage the implementation of best management practices on sheep farms in Ireland. There were 4,500 participants in this programme in 2013. As part of this programme, farmers had the option to carry out a drench test to establish the efficacy of their anthelmintic treatment. RESULTS: Flock faecal samples were collected before and after treatment administration and gastrointestinal nematode eggs enumerated. In total there were 1,893 participants in the task, however only 1,585 included both a pre- and post-treatment faecal sample. Of those, 1,308 provided information on the anthelmintic product that they used with 46%, 23% and 28% using a benzimidazole (BZ), levamisole (LEV) and macrocyclic lactone (ML) product respectively. The remaining farmers used a product inapplicable for inclusion in the task such as a flukicide or BZ/LEV combination product. Samples were included for analysis of drench efficacy if the pre-treatment flock egg count was ≥200 eggs per gram and the interval post-sampling was 10–14 days for BZ products, 4–7 days for LEV products and 14–18 days for ML products. These criteria reduced the number of valid tests to 369, 19.5% of all tests conducted. If the reduction post-treatment was ≥95% the treatment was considered effective. Only 51% of treatments were considered effective using this criterion. There was a significant difference in efficacy between the anthelmintic drug classes with BZ effective in only 30% of treatments, LEV effective in 52% of cases and ML effective in 76% of cases. CONCLUSIONS: Gastrointestinal nematode anthelmintic treatments, as practiced on Irish farms, have a high failure rate. There was a significant difference between the efficacies of the anthelmintic classes with BZ the least effective and ML the most effective.